Unprecedented reactivity of an aluminium hydride complex with ArNH2BH3: nucleophilic substitution versus deprotonation - Harder, Sjoerd; Spielmann, Jan (Chemical Communications, 2011)
Reaction of DIPPnacnacAlH with DIPPNH BH did not give the anticipated deprotonation but nucleophilic substitution at B was observed instead. The product DIPPnacnacAl(BH ) was isolated and structurally characterized. Nucleophilic displacement at B might play a role in mechanistic pathways related to metal amidoborane complexes. © 2011 The Royal Society of Chemistry.